Impacts of high temperature during early capped brood on pupal development and the size of appendages in adult workers Apis cerana - Xu, Xinjian; Du, Xia; Zhou, Shujing; Zhou, Bingfeng; Lai, Kang; Wang, Qing; Li, Han; Zhu, Chenyu; Xu, Hongzhi; Zhang, Xianlan; Cao, Mingjie; Zhu, Xiangjie (Frontiers in Ecology and Evolution, 2023)
Abstract: Pupation is a critical period in the development of holometabolous insects, characterized by the transition from larva to pupa. To understand the sensitivity of honeybee pupation to high temperature, mature larva (ML, on the first day of capping), the first and the second day of pre-pupa (PP1 and PP2), and the first day of pupa (P1) were exposed to 40ºC for hours. The effect of high temperature on mortality, development duration, and the birth weight, the size of body and appendages of eclosed worker bees Apis cerana were analyzed. The results showed that PP1 had the highest mortality, the least birth weight and its longest development duration among the pupation stages. Exposed to 40ºC for 12 h and 16 h, more than 28% and 84%, respectively, PP1 failed to complete development. High-temperature treatment on pupation stages had significant effects on the length of proboscis, the size of the forewing and hind leg. Our results indicated that ML and PP1 were crucial checkpoints for wing and appendages (proboscis and legs) development. This study provides insights into stage specific susceptibility to high temperature stress in a global warming context.